Exploring Shades of Corruption Tolerance: Tentative Lessons from Iceland and Sweden - Erlingsson, Gissur Ólafur; Kristinsson, Gunnar Helgi (Kyiv-Mohyla Law and Politics Journal, 2019)
The aim of this paper is to explore the effects of corruption tolerance on corruption levels. Strong claims are made in the literature to the effect that tolerance of corruption is universally low. We show, however, that there are non-trivial variations in tolerance of corruption, and that these are significantly related to commonly used indices of corruption. This suggests that understanding which factors shape corruption tolerance is important. Here, our concern is with the effects of elite structures on corruption. We first ask if closeness to power affects corruption tolerance and if the general population is less tolerant than elite groups. We then ask if different elite groups — e. g., politicians and civil servants respectively — are likely to form different standards regarding corruption. To hold certain external variables constant, the paper focuses on two relatively homogeneous, low-corruption countries: Sweden and Iceland. Our findings suggest that whereas little supports the closeness to power hypothesis — the general population is not less tolerant of corruption than elites — there may be important differences in how different elite groups within these countries view corrupt activities. This has implications for how corruption can be contained.